Дидактичні особливості викладання дисципліни "Фізична культура та психофізіологічний тренінг" магістрантам спеціальності "Педагогіка вищої школи" - Ігнатюк, Ольга Анатоліївна (НТУ "ХПІ", 2015)
У статті розкрито дидактичні особливості організації вивчення магістрантами навчальної дисципліни "Фізична культура і психофізіологічний тренінг". Розкрито зміст дисципліни, форми і методи професійної підготовки, які сприяють формуванню у магістрантів знань індивідуальних особливостей особистості та практичних навичок їх саморозвитку психічних функцій і саморегуляції емоційних станів, що визначають сутність управлінської ортобіотики. Обговорюються творча складова індивідуальних завдань магістрантів, можливі стратегії і тактики особистісно-професійного амовдосконалення.

The article is devoted to improving the quality of the university system of education, training and competitive mobile graduates. The purpose of the article is to consider the features of didactic teaching called academic discipline, namely clarifying the nature ortobiotik management, its importance to the subjects of educational process and practical steps that will determine the effectiveness of the process of creative self-development on the example of the master's program students specialty "Pedagogy of Higher Education". The author reveals the didactic features of the organization studying the masters of the discipline "Physical training and psychophysiological training" in the article. The questions of advanced training undergraduate’s specialty "Pedagogy of Higher Education" are in the focus of the article. The author draws attention to the role of disciplinary knowledge and practical skills for the subjects of the educational process. The article deals with teaching undergraduates studying the characteristics of the organization of educational discipline "Physical education and psycho-physiological training". It is shown that undergraduates understand the essence of professional educator and a list of professionally important qualities that characterize the creative personality of the teacher researcher. Disclosure of discipline forms and methods of training, contributing to the formation of undergraduates have knowledge of individual personality traits and skills of self-development of mental functions and self-regulation of emotional states that define the essence of management ortobiotik. In developing training plans for individual participants recommended to adhere to the criteria of "SPIRO": specifity, performance, involvement, realism, observability. The creative component of individual tasks undergraduates aimed at personal and professional development and selfimprovement themselves as future teachers, possible strategies and tactics of personal and professional self-improvement are discussed in the article.
Didactic features of teaching discipline "Physical activity and psychophysiological training" undergraduates specialty "Pedagogy of higher education"
Keywords: вища технічна освіта; професійна освіта; етапи навчання; магістрант; модель навчання; педагогічна діяльність; практичні навички; професійно важливі якості; професійні знання; самокероване навчання; управлінська ортобіотика; educational activities; practical skills; professional qualities; professional knowledge; way of preparation; essence of management ortobiotik; training model; self-directed learning undergraduate